Preventing recurrent miscarriage of unknown aetiology. (19th April 2013) - Morley, Lara; Shillito, Jayne; Tang, Thomas
<x xml:space="preserve">Abstract</x> Key content One to three per cent of couples are affected by recurrent miscarriage (defined as more than three consecutive pregnancy losses). Current interventions are centred on known causes of aetiology. Recent research on miscarriage of unknown cause has investigated the requirements for successful embryo implantation. Treatment of immunological risk factors with immunotherapy does not have a strong evidence base. The overall evidence supporting the use of human chorionic gonadotrophin supplementation during pregnancy is inconclusive. The efficacy of progesterone as an intervention remains empirical, with further trials under way. Learning objectives To understand the aetiology of recurrent miscarriage and patient risk factors. To understand the theoretical pathophysiology underlying miscarriage of unknown aetiology. To be aware of the potential agents of intervention for recurrent miscarriage and their efficacy. Ethical issues Treating patients with recurrent miscarriage can be emotive; should women be treated with interventions that have limited evidence‐based clinical efficacy? How do we manage patients with the psychological impact of recurrent miscarriage?